2009
DOI: 10.5012/bkcs.2009.30.8.1755
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Tetrahydrothiophene and Thiophene Self Assembled Monolayers on Au(111): Structure and Molecular Orientation

Abstract: Surface structure and molecular orientation of self-assembled monolayers (SAMs) formed by the spontaneous adsorption of tetrahydrothiophene (THT) and thiophene (TP) on Au(111) were investigated by means of scanning tunneling microscopy (STM) and carbon K-edge near edge X-ray absorption fine structure (NEXAFS) spectroscopy. STM imaging revealed that THT SAMs have a commensurate (3 × 2√3) structure containing structural defects in ordered domains, whereas TP SAMs are composed of randomly adsorbed domains and pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…Similar XPS and NEXAFS results for thiophene reported by Noh et al. ,, showed an S 2p 3/2 peak at 162 eV with a smaller structure at about 161 eV. They concluded that thiophene SAMs form through chemical interaction between the sulfur headgroups in thiophene and the Au(111) surface, but we do not clearly interpret this as due to C–S bond breaking at room temperature.…”
Section: Introductionsupporting
confidence: 63%
See 3 more Smart Citations
“…Similar XPS and NEXAFS results for thiophene reported by Noh et al. ,, showed an S 2p 3/2 peak at 162 eV with a smaller structure at about 161 eV. They concluded that thiophene SAMs form through chemical interaction between the sulfur headgroups in thiophene and the Au(111) surface, but we do not clearly interpret this as due to C–S bond breaking at room temperature.…”
Section: Introductionsupporting
confidence: 63%
“…At room temperature, STM imaging reveals interesting paired row ordered structures, suggesting differently coordinated molecules, which could explain the observation of the two CLBEs mentioned above . In their more recent work they concluded that although they do not observe a peak in NEXAFS at 285.6 eV the 162 eV CLBE corresponds to the bonding of an undissociated thiophene molecule. They affirm this on the basis of observation of ordered structures in STM for thiophene and tetrahydrothiophene (C 4 H 8 S), which has an aliphatic cyclic ring without a π conjugated system.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…The study of self-assembled monolayers (SAMs) has been an attractive field since SAMs allow tailoring of surface properties such as adhesion, corrosion, and biocompatibility, and furthermore, these have been used in research on molecular electronic devices. Historically work on SAMs involved much work on thiols ,,, with the S atom serving as linker to a substrate. Commonly investigated systems involve various thiols with alkane and phenyl groups ,, and also thiophenes. The interaction between the headgroup and substrate affects the characteristics of the SAMs such as orientation, structural configurations, and charge transfer properties and, to a large extent, determines the performance of SAMs. In recent years, therefore, interest in other headgroups as linkers, with possibly better characteristics for a given application, engendered research into molecules bearing heavier chalcogens (Se, Te) as well as other atoms such as N and C. , Several investigations have thus been carried out on selenol SAMs and selenophene adsorption. …”
Section: Introductionmentioning
confidence: 99%